Role of Vitamins D Supplements in Preventing Development of Gestational Diabetes Mellitus - Almas,; Memon, Fahmida Parveen; Bano, Erum; Shamaun, Shamaila; Afsheen, Shahla; Kiran, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To evaluate the role of vitamin D supplements in prevention of gestational diabetes mellitus. Study Design: Cross sectional. Place and duration: Study was carried out at obstetrics and gynecology department of Roshan Suleman Medical College, Tando Adam, from June 10, 2021 to November 09, 2021. Methodology: Initially 125 pregnant women were enrolled in study and 15 women refused to give consent and study was conducted on 110 pregnant women. Main variables of study were age of women, parity, education status, occupation and previous mode of delivery. Outcome of study was gestational diabetes at 28 weeks of glucose tolerance test. SPSS version 23 was used for data analysis, mean and SD for numerical data and frequency percentages for categorical data were calculated. Test of significance was chi square test and p value ≤0.05 was significant. Results: Of the total patients, 40.9% had ≤20 ng/ml and 59.1% had >20 ng/ml level of vitamin D. It was seen that 44.4% patients had ≤20 ng/ml as well as GDM. About 35.6% had normal OGTT with ≤20 vitamin D level. On the other hand, most of the patients 60.0% had normal OGTT as well as >20 ng/ml vitamin D level. The difference had statistically significant, (p=0.005). Conclusion: use of vitamin D supplements in high risk pregnant women till 28 weeks of pregnancy has positive effect on prevention of gestational diabetes.